Event-related delta and theta responses may reflect the valence discrimination in the emotional oddball task - Bölükbaş, Burcu; Aktürk, Tuba; Ardalı, Hilal; Dündar, Yasemin; Güngör, Ceren; Kahveci, Şaika; Güntekin, Bahar (Springer Science and Business Media Deutschland GmbH, 2023)
How emotion and cognition interact is still a matter of debate. Investigation of this interaction in terms of the brain oscillatory dynamics appears to be an essential approach. To investigate this topic, we designed two separate three-stimulus oddball tasks, including emotional stimuli with different valences. Twenty healthy young subjects were included in the study. They completed two tasks, namely: the positive emotional oddball task and the negative emotional oddball task. Each task included the target, non-target, and distractor stimuli. Positive and negative pictures were the target stimuli in the positive and negative emotional oddball task. We asked participants to determine the number of target stimuli in each task. During sessions, EEGs were recorded with 32 electrodes. We found that (negative) target stimuli elicit higher delta (1–3.5 Hz) and theta (4–7 Hz) power responses but not the phase-locking responses compared to (positive) distractor stimuli during the negative oddball task. On the other hand, the same effect was not seen during the positive emotional oddball task. Here, we showed that the valence dimension interacted with the target status. Finally, we summarized our results that the presence of negative distractors attenuated the target effect of the positive stimuli due to the negative bias.
Keywords: Delta Band; Event-Related Oscillations; Negative Bias; Theta Band; Valence Discrimination